Relation between triglycerides associated polymorphisms and lipid profile in Familial Combined Hyperlipidaemia - Santos, T. (2012)
Familial Combined Hyperlipidaemia (FCHL) is a genetic disorder characterized by highly atherogenic profile with prevalence of sdLDL particles, hyperlipidaemia (hypertriglyceridaemia and/or hypercholesterolaemia) and high apoB levels (>120 mg/dL), with different lipid profiles in members of the same family. Some polymorphisms in several genes (LPL -93T>G/D9N, APOAIV Q360H and V13M, APOAV -1131T>C and S19W, APOCIII 3238C>G, USF1s1 and USF1s2) have been associated with higher levels of triglycerides (TG) or FCHL. Hypertriglyceridaemia (HTG) has also been suggested by some authors as an independent risk factor for cardiovascular diseases (CVD).